PO 18195 - Publication trends of research on hallux valgus (1998 - 2018): a bibliometric study - Cristina Stéfani, Kelly; Ferraz Ferreira, Gabriel; Quadros Borges, Vinicius; de Matos Moraes, Leonardo Vinícius (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Hallux valgus (HV) is a very common deformity among affections of the foot, and interest in the subject is persistent in the daily routine of orthopedic surgeons. We investigated the trend in HV publications in the literature. Methods: The research was carried out by searching the Web of Science database between 1998 - 2018, analyzed using a bibliometric methodology. We used the "Bibliometrix" package for R software for the data compilation and VOSviewer for graphic creation. Results: A total of 703 articles were found from the electronic search until December 21, 2018, with 6266 citations. The major scholar in this field was Coughlin M.J., with the largest number of publications (17). The United States led in number of articles published with 26.74%, with Brazil ranked in 26 place. There was an increase in the number of publications, with the highest number of articles published in 2016 (78). Conclusion: The amount of published work on HV has grown rapidly since 2011. The United States has the leading position in global research. The journal with more articles was Foot and Ankle International.